W sieci - czy, po co i jakiej? Relacje w grupach studenckich - komunikat z badań = Online - if, what for, and what? Relationships in student groups - research results - Bochno, Ewa (Zielona Góra: Lubuskie Towarzystwo Naukowe)
This article attempts to analyze the relationships in student groups which are examined from the perspective of the social network category. I investigate the group in relation to the question: if, what for, and what social networking sites do students create within dean`s groups? In the analysis, I focus on the following questions: 1) "?What?", i.e. on the basis of students` information I present basic categories concerning networks, and 2) ?"What`s the result?", i.e. I sketch the specificity of social networks in a group. I end with the summary which refers to the social network categories.
Keywords: relacje międzyludzkie; studenci